Can multi-strategy management stabilize nitrate leaching under increasing rainfall?. (19th December 2019) - Martinez-Feria, Rafael; Nichols, Virginia; Basso, Bruno; Archontoulis, Sotirios
Abstract: The increased spring rainfall intensity and amounts observed recently in the US Midwest poses additional risk of nitrate (NO3 ) leaching from cropland, and contamination of surface and subsurface freshwater bodies. Several individual strategies can reduce NO3 loading to freshwater ecosystems (i.e. optimize N fertilizer applications, planting cover crops, retention of active cycling N), but the potential for synergistic interactions among N management practices has not been fully examined. We applied portfolio effect (PE) theory, a concept originally developed for financial asset management, to test whether implementing multiple N management practices simultaneously produces more stable NO3 leaching mitigation outcomes than what would be predicted from implementing each practice independently. We analyzed simulated data generated using a validated process-based cropping system model (APSIM) that covers a range of soils, weather conditions, and management practices. Results indicated that individual management practices alone explained little of the variation in drainage NO3 loads but were more influential in the amount of residual soil NO3 at crop harvest. Despite this, we observed a general stabilizing effect from adopting well-designed multi-strategy approaches for both NO3 loads and soil NO3 at harvest, which became more pronounced in years with high spring rainfall. We use the PE principle to design multi-strategy management to reduce and stabilize NO3 leaching, which resulted in 9.6% greater yields, 15% less NO3 load, and 61% less soil NO3 at harvest than the baseline typical management. Our results make the case for applying the PE to adapt NO3 leaching mitigation to increased climate variability and change, and guide policy action and on-the-ground implementation.